4m+5=-11

Simple and best practice solution for 4m+5=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m+5=-11 equation:


4m+5=-11

We simplify the equation to the form, which is simple to understand
4m+5=-11

We move all terms containing m to the left and all other terms to the right.
+4m=-11-5

We simplify left and right side of the equation.
+4m=-16

We divide both sides of the equation by 4 to get m.
m=-4

See similar equations:

| 26=6a-10 | | 2=a+12 | | 13x-2=180 | | (x+2)(x-1)=2x | | 4x^5+28x^4+49x^3=0 | | 5(3-2x)+4=3 | | 9x^3-9x^2-4x+4=0 | | kx^2+4x+k=0 | | b-5=-15 | | 2x+7x=9 | | 2x^2-3x+36=11+17x-2x^2 | | B-19=28 | | 5(1+y)-3y=3 | | f(4)=45,000(1+1.67/12)12(4) | | 26=13+x+9 | | 9-2n=3(n+2) | | m=-.25(2,1) | | 36u^2=9 | | 36u=9 | | p=(2a-1)+(a+4)+(2a-1)+(6a-3) | | 34-7x=-57 | | X^2+6x+1=8 | | b-7(b)+6=-30 | | c+1=8 | | 6x+11=2x-45 | | -228=-96+11x | | 14y+5=8y-1 | | 6x+11=2x-4h | | -6(2x-6)=108 | | 1-2x+13=9 | | p=(2a+1)+(a-4)+(2a-1)+(6a-3) | | 7(6x-9)=315 |

Equations solver categories